KUALITAS AIR MANGROVE DITINJAU DARI SIFAT FISIK-KIMIA DI HUTAN MANGROVE PATUNG NGURAH RAI TUBAN DENPASAR SELATAN BALI - Ni Luh Suriani (Master Program of Environmental Science, Postgraduate Program of Udayana University)
The objectives of this research are to find out of mangrove water quality at Patung Ngurah Rai Tuban Denpasar Selatan Baliregarding to physical-chemical . Values of some variables such as total disolved solid, Cromium (Cr), Cadmium (Cd), , Nitrit, and oilwas higher than that of standard quality.This is caused by organic and anorganic waste such as garment factory come from BadungRiver, domestic waste, Ngurah Rai iar Port waste, and car workshop. The inpact of this problem is that the species of mangrove forestis not good condition.